Α‐Mangostin promotes apoptosis of human rheumatoid arthritis fibroblast‐like synoviocytes by reactive oxygen species‐dependent activation of ERK1/2 mitogen‐activated protein kinase. Issue 9 (26th April 2019) - Sheng, Xiaoyun; Li, Jun; Zhang, Chao; Zhao, Lianggong; Guo, Laiwei; Xu, Tianen; Jin, Jiaxin; Wu, Meng; Xia, Yayi
Abstract: α‐Mangostin (α‐M) is a commonly used traditional medicine with various biological and pharmacological activities. Our study aimed to explore the effects and mechanism of α‐M in regulating apoptosis of rheumatoid arthritis fibroblast‐like synoviocytes (RA‐FLS). α‐M of 10 to 100 μM was used to treat RA‐FLS for 24 hours, followed by measuring cell viability and apoptosis. The involvement of reactive oxygen species (ROS) and mitogen‐activated protein kinases was detected. Treatment of α‐M promoted apoptosis and reduced viability of RA‐FLS in a dose‐dependent manner. The mitochondrial membrane potential in RA‐FLS was remarkably reduced by α‐M treatment, accompanied by the cytochrome c accumulation in the cytosol and increased activities of caspase‐3 and caspase‐9. Moreover, we found that α‐M treatment promoted ROS production and extracellular signal‐regulated kinase 1/2 (ERK1/2) phosphorylation. The proapoptotic activity of α‐M in RA‐FLS was markedly reversed by the co‐induction with the ERK1/2 inhibitor LY3214996 or ROS scavenger N ‐acetyl‐l ‐cysteine. In conclusion, our studies found that α‐M had remarkable proapoptotic activities in RA‐FLS, which is regulated by the induction of ROS accumulation and ERK1/2 phosphorylation. α‐M may thus have potential therapeutic effects for rheumatoid arthritis. Abstract : Our studies found that α‐Mangostin (α‐M) had remarkable proapoptotic activities in rheumatoid arthritis fibroblast‐like synoviocytes, which is regulated by the induction of reactive oxygen species accumulation and extracellular signal‐regulated kinase 1/2 phosphorylation. α‐M may thus have potential therapeutic effects for rheumatoid arthritis .